Mirna and Jessica Case on Jakarta Post; Grammatical Cohesion Analysis (Discourse Approach) - Mariyatul Kiptiyah (Penerbit STKIP PGRI Bangkalan, 2017)
Discourse used in linguistics refers to any passage, spoken or written. As the news about “Mirna dan Jessica case” on Jakarta Post. Jakarta Post in one of the News Paper that published in Print out and on-line. In this research the researcher take the data from online news at July 2016. A text in the news include on a passage of discourse which is coherent in these two regards: it is coherent with respect to the context of situation and therefore consistent in register; and it is coherent with respect to itself, and therefore cohesion. This research analyzes the cohesion on the Mirna and Jessica case in Jakarta Post used descriptive design with qualitative method through Discourse approach. The result of the research on grammatical cohesion used in Jakarta post in the first news, are: promonimal reference “her, their, his, and they”, the demonstrative reference “the and that”, Comparative Reference “as”, Cataphoric Reference “another”, Additive Conjunction “and”. For the second news are: Pronominal Reference “Her, she, you, they, their”, Demonstrative Reference “the”, Additive Conjunction “both, and”, Adversative Conjunction “but”